2016
DOI: 10.1177/0306624x16658472
|View full text |Cite
|
Sign up to set email alerts
|

Does Fear of Terrorism Differ From Fear of Crime and Sexual Assault: A Question of Geographical Location and Residential Area

Abstract: The study describes an examination of three types of fear: crime, sexual assault, and terrorism. The sample consisted of 507 adults from three different geographical locations in Israel with different levels of crime and terror attacks. With regard to fear of crime and fear of sexual assault, the results were compatible with the findings of many studies that indicate the effect of residential area features on levels of fear. Fear of terrorism was found to be more complex. The theoretical framework used to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
27
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 63 publications
6
27
0
2
Order By: Relevance
“…Interestingly, it seems that living in the shadow of terrorism or under a constant threat of missiles does not result in higher levels of clinical PTSD. This is compatible with previous studies suggesting that due to the high baseline of pressures and stressors, the Israeli population may in fact experience habituation in the face of repeated exposure (Bensimon et al, ; Shechory Bitton & Cohen Louck, ; Shechory Bitton & Silawi, ).…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, it seems that living in the shadow of terrorism or under a constant threat of missiles does not result in higher levels of clinical PTSD. This is compatible with previous studies suggesting that due to the high baseline of pressures and stressors, the Israeli population may in fact experience habituation in the face of repeated exposure (Bensimon et al, ; Shechory Bitton & Cohen Louck, ; Shechory Bitton & Silawi, ).…”
Section: Discussionsupporting
confidence: 92%
“…The current study intends to expand the field by exploring responses and coping strategies of mothers and fathers residing in towns located in Israel’s Judea and Samaria regions. This area is considered a conflict zone, with residents exposed to a greater number of security threats than most other residents of Israel (Billig, 2015; Shechory-Bitton & Cohen-Louck, 2018). Owing to the fact that parents are exposed to the same threats and potential dangers as their children (Tatar et al, 2011), studies on the coping of fathers and mothers as a family unit while residing in conflict zones will add much-needed further depth to the research field.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive review of the literature indicates several variables can be found related to coping strategies relevant to terrorism exposure and security threats. These include association with scope and frequency of exposure, manner of exposure (direct/indirect), place of residence, age of those exposed, and gender (Besser & Neria, 2012; Braun-Lewensohn & Mosseri Rubin, 2014; Cohen-Louck, 2019; May, Herbert, Cline, & Nellis, 2011; Shechory-Bitton & Cohen-Louck, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Fear is also a key motif in Israeli society, a country that suffers from chronic terrorism. Many Israelis fear the possibility that they or their loved ones will be terrorism victims (Cohen‐Louck, ; Shechory‐Biton & Cohen‐Louck, ), even during relatively quiet periods (Ben‐Dror & Canetti, ). They also felt helplessness (Pat‐Horenczyk, ), perceived terrorist attacks as beyond their personal control, and did not believe they were immune from being hurt by terrorists (Klar, Zakay, & Sharvit, ).…”
Section: Introductionmentioning
confidence: 99%